Ethnic Group Differences in Dietary Diversity of School-Aged Children in Indonesia: The Roles of Gender and Household SES. Issue 2 (June 2019) - Kunto, Yohanes Sondang; Bras, Hilde
Background: Despite the importance of dietary diversity for nutritional status, studies on issues surrounding ethnicity and dietary diversity in developing countries are limited. Objective: We analyzed cross-ethnic differences in dietary diversity and examined the roles of gender and household socioeconomic status (SES) in 3 Indonesian ethnic groups with different kinship systems: Javanese (bilateral), Batak (patrilineal), and Minangkabau (matrilineal). Methods: Data were from the Indonesian Family Life Survey 2000-2015 that consisted of 6478 school-aged children (7-12 years of age) born to 3878 mothers. The children's dietary diversity was measured using a Berry-Index. We used cluster-robust multivariate linear regression models. Results: Gendered dietary diversity occurred for ethnic groups with unilineal kinship but was less evident for ethnic with bilateral kinship. Batak and Minangkabau girls, rather than boys, had higher dietary diversity because boys from these 2 ethnic groups consumed low-status foods (eg, tubers and vegetables) less often. Household SES influenced ethnic-related dietary diversity differently, perhaps because of food culture. Batak children from lower SES households consumed fruits and dairy products less often, most likely to enable them to consume the pricier but culturally preferable animal-source foods. This lowered their dietary diversity. Conclusion: The overall results indicate gendered and household SES-related effects of ethnicity on dietary diversity. Nutrition interventions targeting boys should be on policy-makers' agendas. Boys should be advised to consume healthy low-status foods more often to improve their dietary diversity. The Batak case shows that children from lower SES backgrounds should depend less on the pricier foods to enable them varying their diet better.